A method for preparing long-cycle graphite negative electrode material for lithium-ion batteries
By fluorinating artificial graphite and island-like coating of LiAlO2 solid electrolyte, the volume expansion and SEI film rupture of graphite negative electrode materials in lithium-ion batteries is solved, which extends the battery cycle life and improves the Battery stability and performance.
Patent Information
- Application Number
- CN202410883598.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-03
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-07-03
AI Technical Summary
During the charging and discharging of lithium ions, the graphite negative electrode material in lithium-ion batteries expands and contracts in volume due to the embeddedness and disengagement of lithium ions, resulting in rupture and regeneration of SEI film, consumes active lithium and reduces cycle life.
By fluorinating artificial graphite, doping F elements, and coating LiAlO2 solid electrolyte islandically on its surface, a stable and reliable lithium ion channel is formed to buffer internal stress during the cycle and avoid cracks in the solid electrolyte layer.
It extends the cycle life of lithium-ion batteries, maintains battery capacity, and improves the charging and discharging performance and stability of the battery.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary battery materials, and more specifically, relates to a method for preparing a long-cycle graphite negative electrode material for lithium-ion batteries. Background Art
[0002] As the negative electrode material of lithium-ion batteries, graphite has high theoretical capacity, excellent cycle stability and low cost, so it is widely used in commercial lithium-ion batteries. However, during the battery charging and discharging process, the graphite negative electrode will expand and shrink in volume. This cyclic expansion is one of the important reasons for the reduction of the cycle life of lithium batteries.
[0003] During the first charge and discharge process, the electrolyte undergoes a reduction reaction on the surface of the graphite negative electrode to form a solid electrolyte interface (SEI) layer. This SEI layer is crucial to the stability and cycle life of the battery. If the SEI layer is unstable, it will continue to break and reform during the lithium ion insertion and extraction process, consuming the electrolyte and increasing the internal resistance of the battery, resulting in a decrease in battery performance.
[0004] The volume expansion of the graphite negative electrode during the charge and discharge process may cause stress between the graphite particles. As the number of cycles increases, these stresses may cause the graphite particles to break and fall off, or the negative electrode plates to crack, reducing the effective active materials or requiring continuous consumption of active lithium, thereby reducing the battery capacity and cycle life.
[0005] The volume expansion of the graphite negative electrode may intensify the decomposition of the electrolyte on the negative electrode surface, producing gas and insoluble solid products. These by-products not only consume lithium ions, but may also block the transmission channels of lithium ions, affecting the charge and discharge performance of the battery. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the problem that when the existing graphite is used as the negative electrode material of a lithium ion battery, during use, the embedding and extraction of lithium ions will cause the graphite negative electrode to expand and contract, thereby causing the SEI film on the surface of the negative electrode sheet or active material to continuously rupture and regenerate, ultimately resulting in continuous consumption of active lithium, thereby causing a decrease in cycle life. A method for preparing a long-cycle graphite negative electrode material for a lithium ion battery is provided.
[0007] The purpose of the present invention is to provide a method for preparing a long-cycle graphite negative electrode material for lithium-ion batteries.
[0008] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0009] A method for preparing a long-cycle graphite negative electrode material for a lithium-ion battery, the specific preparation steps comprising:
[0010] Artificial graphite fluorination:
[0011] Fluorinating the artificial graphite to dope the surface of the artificial graphite with F element to obtain fluorinated artificial graphite;
[0012] Solid electrolyte coating:
[0013] LiAlO2 solid electrolyte is coated on the surface of fluorinated artificial graphite negative electrode;
[0014] Wherein, when the LiAlO2 solid electrolyte is coated on the surface of the fluorinated artificial graphite, it is coated in an island shape.
[0015] The above technical solution first fluorinates the artificial graphite to dope the F element on its surface, so that the polarity of the surface of the artificial graphite can be changed, so that the surface of the artificial graphite has a more excellent hydrophilicity at the F element doping point, which is conducive to the subsequent deposition of the precursor of the LiAlO2 solid electrolyte on the surface of the artificial graphite. Specifically, its precursor is more inclined to form an island-shaped coating at the F element doping point. In this way, on the one hand, a stable and reliable fast lithium ion channel is formed between the solid electrolyte and the artificial graphite; on the other hand, the solid electrolyte layer and the artificial graphite can be firmly combined to avoid affecting the bonding state of the solid electrolyte on the surface of the artificial graphite during the manufacturing process of the negative electrode sheet of the battery and the rolling process, causing it to fall off; at the same time, it can also avoid the internal pressure generated by the rebound expansion and contraction of the electrode sheet during the charge and discharge cycle of the battery, which causes the surface solid electrolyte layer to gradually peel off and fail;
[0016] Furthermore, the inventors have found that if artificial graphite is excessively coated, especially if a continuous coating layer is formed, during the use of the battery, as the SEI film is formed, its bonding basis is the aforementioned solid electrolyte layer. Due to the excessive rigidity of the solid electrolyte, the solid electrolyte layer serving as the bonding basis will be prone to cracks during long-term cycles, resulting in continuous consumption of active Li to generate the SEI film. This will cause the active lithium to be continuously consumed and the cycle life to decrease. Through island coating, part of the SEI film in the system is deposited on the surface of the signed solid electrolyte layer, and part of it is deposited on the surface of the artificial graphite. In this way, the part directly deposited on the surface of the artificial graphite can effectively serve as a buffer part to buffer the internal stress during the cycle and avoid the loss of active lithium caused by cracks in the solid electrolyte layer.
[0017] Further, the artificial graphite fluorination comprises:
[0018] First, artificial graphite is ultrasonically dispersed in a sodium fluoride solution to peel off the artificial graphite sheet structure;
[0019] The ultrasonic dispersion is continued for 3-5 hours at an ultrasonic frequency of 180-200 kHz;
[0020] Filter by suction, collect the filter cake, and dry to remove moisture to obtain a dry filter cake;
[0021] The dried filter cake is heated to 580-600°C in a fluorine atmosphere, reacted at high temperature for 4-6 hours, cooled and discharged to obtain fluorinated artificial graphite.
[0022] Through the above treatment process, firstly, under the action of high-power ultrasound, the cavitation effect produced will cause the interlayer spacing of the artificial graphite to be significantly widened, so that in the subsequent F element doping process, the F element can be fully and evenly doped in different parts of the artificial graphite, and finally CF chemical bonds are formed on the surface and inside of the artificial graphite, so that the doped F element can be firmly formed on the surface of the artificial graphite in the form of chemical bonds.
[0023] Furthermore, the mass fraction of the sodium fluoride solution is 8-10%; and, before the ultrasonic dispersion, the method further comprises adding 0.3-0.5% of the mass fraction of the sodium fluoride solution of sodium dodecylbenzene sulfonate to the sodium fluoride solution.
[0024] Furthermore, the fluorine gas atmosphere is a mixture of nitrogen and fluorine in a volume ratio of 10:1-12:1.
[0025] The above technical solution adjusts the amount of F-containing raw materials in the specific preparation process. In this way, combined with the overall preparation process, the doping amount of F element on the surface of artificial graphite can be adjusted to avoid excessive doping, which makes it difficult to form island-shaped coatings during the subsequent solid electrolyte layer deposition process.
[0026] Furthermore, the solid electrolyte coating includes:
[0027] The water-soluble aluminum salt and lithium salt are mixed and dissolved in water, and then fluorinated artificial graphite is added. After ultrasonic dispersion, the pH is adjusted to 7.6-8.0, and the mixture is allowed to stand and age to form a gel. After drying, the mixture is calcined at high temperature, cooled, and discharged to complete the coating of the solid electrolyte.
[0028] Furthermore, the water-soluble aluminum salt is selected from any one of aluminum nitrate, aluminum chloride, aluminum sulfate, and aluminum acetate; the water-soluble lithium salt is selected from any one of lithium nitrate, lithium chloride, and lithium oxalate.
[0029] Furthermore, the total mass of the water-soluble aluminum salt and the water-soluble lithium salt is 6-8% of the mass of the fluorinated artificial graphite, and the molar ratio of Al in the water-soluble aluminum salt to Li in the water-soluble lithium salt is 1:1.05.
[0030] By adjusting the amount and ratio of Li source and Al source in the raw materials, the island coating of solid electrolyte on the surface of artificial graphite can be controlled.
[0031] Further, the step of standing and aging to form a gel comprises:
[0032] At a temperature of 85-95°C, allow to age for 10-12 hours.
[0033] Further, the high temperature calcination includes:
[0034] In a nitrogen atmosphere, heat to 780-800°C at a rate of 5-10°C / min, keep warm and calcine for 5-6 hours, cool to room temperature with the furnace, and discharge the material, thus completing the high-temperature calcination. DETAILED DESCRIPTION
[0035] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0036] Unless otherwise specified, the reagents and materials used in the following examples are commercially available. Example 1
[0037] Artificial graphite fluorination:
[0038] Firstly, artificial graphite is added into a sodium fluoride solution, and then 0.3% of sodium dodecylbenzene sulfonate by mass of the sodium fluoride solution is added, followed by ultrasonic dispersion to exfoliate the artificial graphite sheet structure, thereby obtaining a dispersion;
[0039] The mass fraction of the sodium fluoride solution is 8%;
[0040] The ultrasonic dispersion is continued for 3 hours at an ultrasonic frequency of 180 kHz;
[0041] The obtained dispersion was then transferred into a Buchner funnel for suction filtration, and the filter cake was collected. The obtained filter cake was transferred into an oven and dried at 100° C. to a constant weight to obtain a dry filter cake.
[0042] The obtained dried filter cake was then transferred into a tube furnace, and a fluorine-containing gas was introduced into the furnace at a rate of 30 L / min, wherein the fluorine-containing gas was a mixture of nitrogen and fluorine in a volume ratio of 10:1;
[0043] Then, the temperature was raised to 580°C at a rate of 5°C / min in a fluorine atmosphere, and the high temperature reaction was maintained for 4 hours, and then the furnace was naturally cooled to room temperature, and the material was discharged to obtain fluorinated artificial graphite;
[0044] Solid electrolyte coating:
[0045] Mix and dissolve water-soluble aluminum salt and lithium salt in water, and then add fluorinated artificial graphite;
[0046] The total mass of the water-soluble aluminum salt and the water-soluble lithium salt is 6% of the mass of the fluorinated artificial graphite, and the molar ratio of Al in the water-soluble aluminum salt to Li in the water-soluble lithium salt is 1:1.05.
[0047] After the addition of fluorinated artificial graphite is completed, ultrasonic dispersion is performed for 3 hours at an ultrasonic frequency of 65 kHz, and the pH is adjusted to 7.6. Then, the mixture is aged for 10 hours at a temperature of 85°C to form a gel. The obtained gel is then dried to remove the solvent. Then, the mixture is heated to 780°C at a rate of 5°C / min in a nitrogen atmosphere, calcined for 5 hours, cooled to room temperature with the furnace, and discharged, thereby completing the coating of the solid electrolyte; thus, a long-cycle graphite negative electrode material for lithium-ion batteries is obtained.
[0048] The water-soluble aluminum salt is selected from aluminum nitrate; the water-soluble lithium salt is selected from lithium nitrate. Example 2
[0049] Artificial graphite fluorination:
[0050] Firstly, artificial graphite is added into a sodium fluoride solution, and then 0.4% of sodium dodecylbenzene sulfonate by mass of the sodium fluoride solution is added, followed by ultrasonic dispersion to exfoliate the artificial graphite sheet structure, thereby obtaining a dispersion;
[0051] The mass fraction of the sodium fluoride solution is 9%;
[0052] The ultrasonic dispersion is continued for 4 hours at an ultrasonic frequency of 190 kHz;
[0053] The obtained dispersion was then transferred into a Buchner funnel for suction filtration, and the filter cake was collected. The obtained filter cake was transferred into an oven and dried at 100° C. to a constant weight to obtain a dry filter cake.
[0054] The obtained dried filter cake was then transferred into a tube furnace, and a fluorine-containing gas was introduced into the furnace at a rate of 32 L / min, wherein the fluorine-containing gas was a mixture of nitrogen and fluorine in a volume ratio of 11:1;
[0055] Then, the temperature was raised to 590°C at a rate of 5°C / min in a fluorine atmosphere, and the high temperature reaction was maintained for 5 hours, and then the furnace was naturally cooled to room temperature, and the material was discharged to obtain fluorinated artificial graphite;
[0056] Solid electrolyte coating:
[0057] Mix and dissolve water-soluble aluminum salt and lithium salt in water, and then add fluorinated artificial graphite;
[0058] The total mass of the water-soluble aluminum salt and the water-soluble lithium salt is 7% of the mass of the fluorinated artificial graphite, and the molar ratio of Al in the water-soluble aluminum salt to Li in the water-soluble lithium salt is 1:1.05.
[0059] After the addition of fluorinated artificial graphite is completed, ultrasonic dispersion is performed for 3 hours at an ultrasonic frequency of 65kHz, and the pH is adjusted to 7.8. Then, the mixture is aged for 11 hours at a temperature of 90°C to form a gel. The obtained gel is then dried to remove the solvent. Then, the mixture is heated to 790°C at a rate of 8°C / min in a nitrogen atmosphere, calcined for 5.5 hours, cooled to room temperature with the furnace, and discharged, thereby completing the coating of the solid electrolyte; thus, a long-cycle graphite negative electrode material for lithium-ion batteries is obtained.
[0060] The water-soluble aluminum salt is selected from aluminum chloride; the water-soluble lithium salt is selected from lithium chloride. Example 3
[0061] Artificial graphite fluorination:
[0062] Firstly, artificial graphite is added into a sodium fluoride solution, and then 0.5% of sodium dodecylbenzene sulfonate by mass of the sodium fluoride solution is added, followed by ultrasonic dispersion to exfoliate the artificial graphite sheet structure, thereby obtaining a dispersion;
[0063] The mass fraction of the sodium fluoride solution is 10%;
[0064] The ultrasonic dispersion is continued for 5 hours at an ultrasonic frequency of 200 kHz;
[0065] The obtained dispersion was then transferred into a Buchner funnel for suction filtration, and the filter cake was collected. The obtained filter cake was transferred into an oven and dried at 100° C. to a constant weight to obtain a dry filter cake.
[0066] The obtained dried filter cake was then transferred into a tube furnace, and a fluorine-containing gas was introduced into the furnace at a rate of 35 L / min, wherein the fluorine-containing gas was a mixture of nitrogen and fluorine in a volume ratio of 12:1;
[0067] Then, the temperature was raised to 600°C at a rate of 5°C / min in a fluorine atmosphere, and the high temperature reaction was maintained for 6 hours, and then the furnace was naturally cooled to room temperature, and the material was discharged to obtain fluorinated artificial graphite;
[0068] Solid electrolyte coating:
[0069] Mix and dissolve water-soluble aluminum salt and lithium salt in water, and then add fluorinated artificial graphite;
[0070] The total mass of the water-soluble aluminum salt and the water-soluble lithium salt is 8% of the mass of the fluorinated artificial graphite, and the molar ratio of Al in the water-soluble aluminum salt to Li in the water-soluble lithium salt is 1:1.05.
[0071] After the addition of fluorinated artificial graphite is completed, ultrasonic dispersion is performed for 3 hours at an ultrasonic frequency of 65 kHz, and the pH is adjusted to 8.0. Then, the mixture is aged for 12 hours at a temperature of 95°C to form a gel. The obtained gel is then dried to remove the solvent. Then, the mixture is heated to 800°C at a rate of 10°C / min in a nitrogen atmosphere, calcined for 6 hours, cooled to room temperature with the furnace, and discharged, thereby completing the coating of the solid electrolyte; thus, a long-cycle graphite negative electrode material for lithium-ion batteries is obtained.
[0072] The water-soluble aluminum salt is selected from aluminum sulfate; the water-soluble lithium salt is selected from lithium oxalate. Example 4
[0073] The present embodiment differs from Embodiment 1 in that the fluorine-containing gas is a mixture of nitrogen and fluorine in a volume ratio of 8:1.
[0074] Comparative Example 1
[0075] Compared with Example 1, this comparative example has the following differences:
[0076] Fluorinated artificial graphite is directly used as the long-cycle graphite negative electrode material for lithium-ion batteries without being wrapped with solid electrolyte, and other conditions remain unchanged.
[0077] Comparative Example 2
[0078] Compared with Example 1, this comparative example has the following differences:
[0079] The artificial graphite was directly coated with solid electrolyte without fluorination treatment, and the other conditions remained unchanged.
[0080] The performance tests were performed on the products obtained in Examples 1-4 and Comparative Examples 1-2. The specific test methods and test results are as follows:
[0081] The products obtained in the above embodiments or comparative examples were used as negative electrode active materials, respectively. The negative electrode active material, conductive carbon black Super-P and carboxymethyl cellulose were mixed in a mass ratio of 9:0.5:0.5, and deionized water was added as a solvent. The mixture was stirred at a speed of 300 r / min for 12 h to prepare a negative electrode slurry. Subsequently, the negative electrode slurry was scraped on the surface of the copper foil, and dried at 100° C. for 12 h to obtain a negative electrode sheet, which was cut into discs with a diameter of 12 mm. The surface density of the active material on the surface of the negative electrode sheet was controlled at 2.75 mg / cm 2; In a glove box, a CR2032 battery shell was selected, a lithium sheet was used as a counter electrode and a reference electrode, and a porous polypropylene membrane (Clegard 2320) was used as a diaphragm. A button-type half-cell was assembled in the order of a negative electrode sheet, a diaphragm, an electrolyte, a lithium sheet, a gasket, and a shell, wherein the electrolyte was selected as a ternary mixture of 1 mol / L lithium hexafluorophosphate dissolved in ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in a volume ratio of 1:1:1; after the battery was assembled and sealed, it was allowed to stand at room temperature for 36 hours to perform electrochemical performance testing; a CT2001A blue electric test system was used with a test voltage range of 0.005-3.0V to perform a constant current charge and discharge test on the above-mentioned battery. After 500 cycles of continuous charge and discharge, the capacity retention rate of the battery corresponding to each embodiment or comparative example product was tested; AUTOLAB The battery was subjected to a cyclic voltammetry test using a PGSTAT302N electrochemical workstation, with a test range of 0-3V and a scan rate of 0.1 mV / s, to obtain the first coulombic efficiency of the battery corresponding to each embodiment or comparative example product; the specific test results are shown in Table 1;
[0082] Table 1: Product performance test results
[0083] Capacity retention rate / % First coulombic efficiency / % Example 1 99.32 95.76 Example 2 99.38 95.68 Example 3 99.36 95.71 Example 4 98.05 94.01 Comparative Example 1 95.52 92.12 Comparative Example 2 93.21 92.22
[0084] It can be seen from the test results in Table 1 that when the product obtained by the present invention is applied to lithium-ion batteries, excellent first coulombic efficiency can be obtained, and with long-term charge and discharge cycles, its capacity can be effectively maintained, which can effectively extend the service life of the product.
[0085] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a long-cycle graphite negative electrode material for a lithium-ion battery, characterized in that: The specific preparation steps include: Artificial graphite fluorination: Fluorinating the artificial graphite to dope the surface of the artificial graphite with F element to obtain fluorinated artificial graphite; Solid electrolyte coating: LiAlO2 solid electrolyte is coated on the surface of fluorinated artificial graphite negative electrode; Wherein, when the LiAlO2 solid electrolyte is coated on the surface of the fluorinated artificial graphite, it is coated in an island shape.
2. The method for preparing a long-cycle graphite negative electrode material for a lithium-ion battery according to claim 1, characterized in that: The artificial graphite fluorination comprises: First, artificial graphite is ultrasonically dispersed in a sodium fluoride solution to peel off the artificial graphite sheet structure; The ultrasonic dispersion is continued for 3-5 hours at an ultrasonic frequency of 180-200 kHz; Filter by suction, collect the filter cake, and dry to remove moisture to obtain a dry filter cake; The dried filter cake is heated to 580-600°C in a fluorine atmosphere, reacted at high temperature for 4-6 hours, cooled and discharged to obtain fluorinated artificial graphite.
3. The method for preparing a long-cycle graphite negative electrode material for a lithium-ion battery according to claim 2, characterized in that: The mass fraction of the sodium fluoride solution is 8-10%; and the method further comprises adding 0.3-0.5% of the mass fraction of the sodium fluoride solution of sodium dodecylbenzene sulfonate to the sodium fluoride solution before the ultrasonic dispersion.
4. The method for preparing a long-cycle graphite negative electrode material for a lithium-ion battery according to claim 3, characterized in that: The fluorine gas atmosphere is formed by mixing nitrogen gas and fluorine gas in a volume ratio of 10:1-12:
1.
5. The method for preparing a long-cycle graphite negative electrode material for a lithium-ion battery according to claim 1, characterized in that: The solid electrolyte coating comprises: The water-soluble aluminum salt and lithium salt are mixed and dissolved in water, and then fluorinated artificial graphite is added. After ultrasonic dispersion, the pH is adjusted to 7.6-8.0, and the mixture is allowed to stand and age to form a gel. After drying, the mixture is calcined at high temperature, cooled, and discharged to complete the coating of the solid electrolyte.
6. The method for preparing a long-cycle graphite negative electrode material for a lithium-ion battery according to claim 5, characterized in that: The water-soluble aluminum salt is selected from any one of aluminum nitrate, aluminum chloride, aluminum sulfate, and aluminum acetate; the water-soluble lithium salt is selected from any one of lithium nitrate, lithium chloride, and lithium oxalate.
7. The method for preparing a long-cycle graphite negative electrode material for lithium-ion batteries according to claim 6, characterized in that: The total mass of the water-soluble aluminum salt and the water-soluble lithium salt is 6-8% of the mass of the fluorinated artificial graphite, and the molar ratio of Al in the water-soluble aluminum salt to Li in the water-soluble lithium salt is 1:1.
05.
8. The method for preparing a long-cycle graphite negative electrode material for a lithium-ion battery according to claim 5, characterized in that: The static aging to form a gel comprises: At a temperature of 85-95°C, allow to age for 10-12 hours.
9. The method for preparing a long-cycle graphite negative electrode material for a lithium-ion battery according to claim 5, characterized in that: The high temperature calcination comprises: In a nitrogen atmosphere, heat to 780-800°C at a rate of 5-10°C / min, keep warm and calcine for 5-6 hours, cool to room temperature with the furnace, and discharge the material, thus completing the high-temperature calcination.
Citation Information
Patent Citations
LiAlO2 coated modified graphite negative electrode material as well as preparation method and application thereof
CN113363446A
Long-life graphite composite material and preparation method thereof
CN115275166A